Masjid Ampel di Amlapura Karangasem: Salah Satu Bukti Keberadaan Islam di Pulau Dewata - Asep Saefulah (Jurnal Lektur Keagamaan, 2013)
Ampel Mosque of Amlapura, Karangasem is one of the ancient mosques in the Province of Bali. According to local folklore, the mosque was built in the 17th century AD. The existence of this mosque shows characteristics of an ancient mosque, which according Pijper often found in Java. Some of the main features of ancient mosques found in the mosque, i.e. massive foundation and rather high and square shaped, rectangular schematics even square, thick-walled, and roofed duplex overlap. It was characterised that Ampel Mosque appeared like the shape of Sunan Ampel mosque Surabaya, East Java, and it also resembled to the two other mosques in Banten province, viz. Caringin Mosque and Al-Khusaini Mosque of Carita, both are in the District of Pandeglang. Ampel Mosque is currently no longer used as a place of worship but is used as a place of religious activities such as religious teaching (Majlis Taklim), Preliminary or preschool education of Al-Qur'an (TPA) and Religious Education (Madrasah Diniyah) . The existence of the ancient mosque of Ampel in this village is one of the historical testimony of the development and spread of Islam in Bali amongst the majority of Hindu population. Keywords: Ampel, ancient mosque, Karangasem, Bali, harmony